Efektivitas Edukasi Gizi Berbasis Teknologi Informasi dalam Pencegahan Stunting: Systematic Literature Review - Mariati Imran; Susilawati Suleman (Jurnal Ilmiah Wahana Pendidikan, 2025)
Stunting remains a major chronic nutritional problem among children under five in Indonesia and other developing countries, with multifactorial causes that include inadequate maternal nutritional knowledge and practices. Advances in information technology provide opportunities for nutrition education interventions that are more interactive, accessible, and capable of reaching wider target populations than conventional methods. This review aimed to systematically examine the effectiveness of information technology-based nutrition education—including mobile applications, websites, social media, digital videos, instant messaging, and e-booklets—in improving knowledge, attitudes, and behaviors related to stunting prevention. Methods: A literature search was conducted using Google Scholar and Scopus-indexed databases, including supporting sources from PubMed, Web of Science, EBSCO, and ProQuest cited in Scopus-indexed articles. Publications from 2021 to 2024 were identified following the PRISMA framework and predefined inclusion and exclusion criteria. A total of 19 primary studies and systematic reviews met the eligibility criteria and were analyzed using a narrative-thematic approach. Most studies demonstrated that information technology-based nutrition education, delivered through Android applications, WhatsApp groups, animated videos, e-booklets, or combinations of social media platforms, consistently improved nutritional knowledge and attitudes among target groups, including pregnant women, mothers of children under five, adolescents, and Posyandu community health volunteers, compared with control groups or pre-intervention conditions. Comparative studies indicated that video-based education tended to be more effective than static printed materials or booklets, while the effectiveness of mobile applications was strongly influenced by intervention duration, interactivity, and the contextualization of content to local needs. Information technology-based nutrition education is an effective strategy for stunting prevention; however, its effectiveness depends on intervention design, the digital literacy of target populations, and the sustained use of digital media.